DAM COLLAPSE ANALYSIS (CASE STUDY: SINDANGHEULA DAM, SERANG REGENCY) - Sudrajat Sudrajat; Bambang Priyambodo; Kristina Sembiring; Cahyadi Cahyadi; Ediyanto Arief (Sean Institute, 2022)
Dam failure is defined as partial or complete collapse of the dam or its complementary structures and/or damage resulting in the non-functioning of the dam. Sindangheula Dam was built across the Cibanten River, which is located in Serut Village, Sindangheula Village, Pabuaran District, Serang Regency, Banten Province with a watershed area (DAS) of 74,46 km2, the length of the main river ± 16 km with a height difference between the highest point and the location of the dam ± 1672 m. Sindangheula dam is designed with a zoned embankment type consisting of the main dam and the koferdam which are integrated into one unit. Both have a zonal type of fill consisting of a vertical core, filter, transition and rockfill. The upstream slope is 1: 3,00 and the downstream slope is 1: 2,50. The dam is designed with an inflow discharge of 1000 th. As for the calculation of the program, according to the procedure, the Probably Maximum Flood (PMF) flood discharge is used of 861,94 m3/second. The main Sindangheula dam is assumed to have collapsed due to overtopping caused by continuous rains and the high discharge is the same as the PMF flood discharge. The hydrological analysis shows that at the PMF flood discharge of 861,94 m3/second, at the spillway crest elevation condition at +106,613 masl, the water will run over the top of the dam (overtopping) causing the dam to collapse completely. From the results of the running model, it can be seen that the pattern of flood flow that occurred due to the collapse of the dam, the flood occurred in almost all downstream of the dam which is an urban and densely populated area with inundation heights reaching 0,10 – 14,90 m, and a flow velocity of 0,01 – 58,16 m/s.